History and religious experience in biblical research - De Villiers, Pieter G. R. (HTS teologiese studies, 2003)
This essay firstly investigates the role of history and religious expe-rience in the research of biblical texts generally and on the Book of Revelation in particular. It delineates limitations of some established historical interpretations and new developments in historical work on the Bible. The second part illustrates these trends by comparing earlier historical readings of Revelation with recent work in which the experiential plays a decisive role. The article argues that where historical scholarship distorts, neglects or excludes the religious dimensions of a text, it fails to understand the true nature of the biblical text and interpretation is skew.